Prospects for the development of SMEs until 2030 as part of the implementation of new national projects - T. A. Shpilkina; O. N. Dolina; N. N. Filimonova; L. S. Artamonova (Путеводитель предпринимателя)
In this publication, the authors investigated the prospects for the development of SMEs until 2030 as part of the implementation of new national projects in Russia, which include: «Family», «Youth of Russia», «Long active life», «Personnel» and «Data Economy».In the course of the study, the authors provided analytical data on the dynamics of SMEs for 2017–2024, the share of SMEs in the country’s GDP, lending to SMEs and their debt in 2024. According to the authors, one of the reasons for limiting SME financing at the expense of credit resources is the continued growth of the discount rate of the Central Bank of the Russian Federation.Positive examples of the development of SMEs in industry with analytical data on their development are given. The most relevant and expected prospects for the development of SMEs until 2030 are presented, taking into account the identified problems and opportunities. The results of this study will allow us to more accurately assess the contribution and importance of small and medium–sized enterprises to the Russian economy.